Nursing support of families and carers of people with dementia - Andrews, June (Henry Stewart Talks, 2017)
The role of a nurse in dementia care, Defining the problem in dementia, Various pathologies underlying dementia symptoms, Interventions in dementia, The leaf model, Acute-care hospitals and people with dementia, Role of the family caregiver in hospital, Hints on behavioural problems of greatest concern, Causes of stress and distress and dealing with them, How to follow the nurse's code for dementia, Ideas of staying well, An action plan for nurses